Covid Photo Diaries : Activism in the visual communication of the Covid-19 pandemic - Martínez Rod, Pamela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
We analyzed the Covid Photo Diaries’s photographs taken during the pandemic to show their disagreement with the photographs of the media. Thus, we recognize two places for photographic production, the official one and Covid Photo Diaries’s, as an activist, for their contribution to the expansion of social representations of the disease from a socio-affective perspective omitted by the global official discourse. This photographs invite us to go beyond the stigmatizing stereotypes of the disease and manage to destabilize the dominant imagery disseminated by the media, to favor the construction of an affective discourse that includes the different human experiences.